2021
DOI: 10.18549/pharmpract.2021.3.2423
|View full text |Cite
|
Sign up to set email alerts
|

Participants’ perceptions of a residency teaching certificate program: the quality, impact and benefits

Abstract: Background: Currently, there are no accreditation requirements for pharmacy resident teaching certificate programs (RTCPs) but rather suggested guidelines and documents for individual programs to follow. RTCP curriculums are often “handed-down” from past personnel and vary based on individual interpretation. Quality improvement may be overlooked when programs do not report to governing bodies. Objective: The primary objective of this quality improvement project was threefold: 1) to identify past RTCP par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…11,[13][14][15][16][17][18][19][20][21][22][23][24][25] Foundation pharmacy residency programs have improved residents' competencies to deliver education and teaching, and to build the foundational skills in becoming strong mentors and preceptors when offered the adequate opportunities. [13][14][15][20][21][22][24][25][26] In the USA, the use of teaching certificate programs for pharmacy residents to gain the knowledge and competencies to deliver pharmacy education and refine their skills in teaching and mentoring has become a core component of residency training. 13,14,17,18,[20][21][22]26 Multiple studies have demonstrated the different teaching and education competencies that residents gain throughout pharmacy residency, and the long-term benefits it has on their career (see Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…11,[13][14][15][16][17][18][19][20][21][22][23][24][25] Foundation pharmacy residency programs have improved residents' competencies to deliver education and teaching, and to build the foundational skills in becoming strong mentors and preceptors when offered the adequate opportunities. [13][14][15][20][21][22][24][25][26] In the USA, the use of teaching certificate programs for pharmacy residents to gain the knowledge and competencies to deliver pharmacy education and refine their skills in teaching and mentoring has become a core component of residency training. 13,14,17,18,[20][21][22]26 Multiple studies have demonstrated the different teaching and education competencies that residents gain throughout pharmacy residency, and the long-term benefits it has on their career (see Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15][20][21][22][24][25][26] In the USA, the use of teaching certificate programs for pharmacy residents to gain the knowledge and competencies to deliver pharmacy education and refine their skills in teaching and mentoring has become a core component of residency training. 13,14,17,18,[20][21][22]26 Multiple studies have demonstrated the different teaching and education competencies that residents gain throughout pharmacy residency, and the long-term benefits it has on their career (see Table 1). As providing education and teaching is becoming more integrated in the work of pharmacists, studies suggest that residencies must work to standardise the teaching programs and provide residents with ample practical opportunities to gain exposure to these skills, such as through increased availability of teaching certificate programs or a specific precepted rotation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations